THE EFFECT OF WORK ENVIRONMENT AND JOB SATISFACTION ON EMPLOYEE PERFORMANCE WITH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE AT THE DEPARTMENT OF POPULATION CONTROL AND FAMILY PLANNING SAROLANGUN REGENCY - Pusparani, Mellysa; Amin, Shopia; Ali, Hapzi (Dinasti Publisher, 2021)
The purpose of this research is to analyze the effect of work environment and job satisfaction on employee performance at the Department of Control and Family Planning, Sarolangun Regency, either directly or indirectly through organizational commitment. The population in this study were employees of the Department of Control and Family Planning, amounting to 94 people. The sampling technique in this study used a saturated sample. This study uses a quantitative approach with survey methods, and uses Partial Least Square (PLS) as a data analysis technique. From the hypothesis testing conducted, it can be concluded that the work environment and job satisfaction affect the performance of the employees of the Sarolangun Regency Family Planning and Control Agency, either directly or indirectly through organizational commitment. These results indicate that if the Sarolangun Regency Family Planning and Control Agency can provide a conducive work environment for its employees, and is also supported by a high level of employee job satisfaction, then this will also be followed by the increasing commitment of employees to be able to work optimally in the organization.